2007
DOI: 10.1007/s11255-007-9289-4
|View full text |Cite
|
Sign up to set email alerts
|

Sperm motility changes after coincubation with various uropathogenic microorganisms: an in vitro experimental study

Abstract: Observed negative impact on sperm motility was not correlated with microorganism concentration. However, until a certain concentration threshold, this impact was prominent. Regardless of the microorganism, this deleterious effect could not be confirmed in specimens coincubated with lower microorganism concentration. No or poor correlation was found between motility and bacteria concentration except with E. aerogenes at the second hour. The data indicates that sperm function impairment is not related to direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 18 publications
(25 reference statements)
0
24
0
3
Order By: Relevance
“…Sperm motility and vitality are decreased in patients with genital tract infection ( Diemer et al., ; Huwe et al ., ; Sanocka‐Maciejewska et al ., ; Berkast et al ., ). Escherichia coli has been isolated from prostatic secretion in 65–80% of chronic bacterial prostatitis cases (Weidner et al ., ) and from semen in 69% of cases of chronic bacterial prostatitis (Weidner et al ., 1991b).…”
Section: Introductionmentioning
confidence: 97%
“…Sperm motility and vitality are decreased in patients with genital tract infection ( Diemer et al., ; Huwe et al ., ; Sanocka‐Maciejewska et al ., ; Berkast et al ., ). Escherichia coli has been isolated from prostatic secretion in 65–80% of chronic bacterial prostatitis cases (Weidner et al ., ) and from semen in 69% of cases of chronic bacterial prostatitis (Weidner et al ., 1991b).…”
Section: Introductionmentioning
confidence: 97%
“…A body of evidence records that a number of species of bacteria exert a negative impact on semen and sperm parameters including motility (Berktas et al ., ; Prabha et al ., ; De Francesco et al ., ), morphology (Eley et al ., ; Zhang et al ., ), concentration (Mazzoli et al ., ), DNA fragmentation (Gallegos et al ., ), acrosome reaction (Gupta & Prabha, ) and increased apoptosis (Eley et al ., ). The presence of bacteria was also recently found to be associated with infertility (Abusarah et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…The results of these studies suggest that the simple presence of bacteria in semen samples may compromise sperm quality (2, 3, 29). However, the majority of the data on the interactions between spermatozoa and bacteria are derived from in vitro studies (30), under conditions that may not accurately mimic in vivo conditions, For example, the bacterial population densities used for in vitro experiments have been much higher than ever recovered from ejaculate specimens (31). In some other studies, these putative pathogenic bacteria were not only found in the reproductive tracts of infertile patients, but also in those of healthy men (25, 26).…”
mentioning
confidence: 99%